PROBLEMATIKA PRODUKSI BIOETANOL DALAM MENDUKUNG SWASEMBADA ENERGI NASIONAL - Muhammad Rizki Azmi Panjaitan; Helda Risman; Mohammad Sidik Boedoyo (PendIPA Journal of Science Education, 2026)
Bioethanol has strategic significance for Indonesia because it integrates renewable energy policy, domestic agricultural resources, sugar industry performance, and national energy security. However, bioethanol cannot be positioned merely as a downstream fuel-blending agenda unless its upstream feedstock system has been verified through reliable data, quality standards, spatial readiness, and bankable supply contracts. This study analyzes the production challenges of bioethanol in supporting national energy self-sufficiency by developing a sequential upstream assessment covering sugarcane plantation distribution, the spatial distribution of 59 active sugar mills, provincial sugar production, actual national molasses production, the estimated molasses baseline for 2025-2026, and molasses trade dynamics.This study employs a descriptive qualitative method supported by a structured literature review. The findings indicate that Indonesia’s sugarcane and sugar production remain spatially concentrated, particularly in East Java and Lampung. Actual national molasses production was recorded at 1.471 million tons in 2020, increased to 1.686 million tons in 2023, and reached 1.636 million tons in 2024. Based on historical sugar-to-sugarcane and molasses-to-sugarcane ratios, baseline molasses availability is estimated at 1.706 million tons in 2025 and 1.773 million tons in 2026. Nevertheless, this volume cannot automatically be regarded as bankable feedstock for bioethanol, since molasses is also absorbed by existing domestic industries and export markets.This article concludes that Indonesia requires a verified national molasses balance, quality-based molasses governance, and stronger integration between sugar and energy policies so that bioethanol can contribute reliably to national energy self-sufficiency.